Theoretical Basis Of Parents' Speech Relationships With Children With Autism (Eurasian Journal of Humanities and Social Sciences, 2025)
This article shows that the concepts of "communication", "activity" are closely related to such a category as "relationship" (Andreeva G. M., 1980; Boda-Lev A. A., 1994; Levchenko E. V., 2003; Leontiev A. A., 1975) [4, 21, 106, 108], on the one hand, the formation and development of relationships occur in the interaction of a person with other people, on the other hand, the relationship itself has a significant impact on the communication process, and although relationships are closely related to communication and activity, they are not limited to communication and joint activities, but represent a "special type of social environment" [167, p. 5]. The theoretical foundations of the concepts of the theoretical foundations of the speech relations of parents with children with autism syndrome are widely covered